The effect of re-engineering banking operations in enhancing internal marketing : Analytical study on the opinions of a sample of workers in commercial in Basra governorate (Entrepreneurship Journal for Finance and Business, 2021)
The research aims to identify the extent of the impact of re-engineering banking operations in strengthening internal marketing , and proposing new mechanisms aimed at overcoming obstacles that stand in the way of developing performance in banks, research sample and working to improve their performance, as the re-engineering of banking operations is a modern method used in implementing changes in banks, therefore the research community was represented by the commercial banks operating in Basra governorate and 6 banks were selected from them, the research sample included a group of 32 employees in these banks, the analysis was based on a solid base that sought to reveal the practices of these banks in how to improve their banking operation, a number of hypotheses related to the influence relationships between the research variables represented by re-engineering banking operations and internal marketing were tested, the data were processed by statistical methods using (SPSS) program, the results of the statistical analysis of the data collected through the questionnaire tool prepared for this purpose showed that there is an impact of the dimensions of the re-engineering of banking operations on the dimensions of internal marketing in banks .